Modelling of street radio links as Microwave Multiports at work of system WIMAX in the conditions of the city - Strelnitskiy, A. A.; Tsopa, A. I.; Shokalo, V. M. (Видавництво Національного університету "Львівська політехніка", 2009)
The approached method of calculation of attenuation of radio-waves along street wave channels with the help canyon radio waves propagation (RWP) models and the Microwave Office packet of applied programs has been developed. The comparative analysis of the results of calculation and experiment for a case of WiMAX system operating in the central area of Kharkiv has been supplied.
Keywords: modelling; attenuation; multi-terminal circuit; dispersion matrix; transmission line